Pengaruh Manajemen Aset Dan Struktur Modal Terhadap Kinerja Perusahaan - Berkat Sumber Jaya Tampubolon; Saiful Saiful (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze the influence of asset management and capital structure on company performance. Asset management is measured by TATO, while capital structure is measured by DAR. Company performance is assessed through return on assets (ROA). The study's population consists of manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The research sample comprises 93 companies selected using purposive sampling. The data analysis technique employed is multiple linear regression with the assistance of SPSS 24 software. The results indicate that asset management has a positive and significant impact on company performance, while capital structure also has a positive and significant influence. The implications of this research suggest that companies should efficiently manage their assets and optimize the use of equity capital rather than relying on debt to enhance overall company performance. Keywords: Company Performance, Asset Management, And Capital Structure